2018
DOI: 10.1039/c8nr07300g
|View full text |Cite
|
Sign up to set email alerts
|

Geometric modulation of induced plasmonic circular dichroism in nanoparticle assemblies based on backaction and field enhancement

Abstract: The interplay between local field enhancement and backaction determines plasmonic chiral responses and leads to widely tunable geometry-dependent optical activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 64 publications
0
30
0
Order By: Relevance
“…However, how to model chiral molecules has been a great challenge in many theoretical studies, among which two approaches are found to show good agreement with experimental observations. [44][45][46][47]60] The first approach was proposed by Govorov based on the density-matrix formalism, where a chiral molecule is treated as a two-level system with nonorthogonal magnetic and electric dipole moments and subsequently the CD spectrum of the hybrid molecule-NC complex can be rigorously calculated as the total contribution from the molecule and the NC. [44,45] In the second approach, Zhang and co-workers simply considered the plasmonic absorption as the dominant contribution to the overall CD of the hybrid system, where the chiral molecule is regarded as an electric dipole with different effective polarizabilities for LCP and RCP excitation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…However, how to model chiral molecules has been a great challenge in many theoretical studies, among which two approaches are found to show good agreement with experimental observations. [44][45][46][47]60] The first approach was proposed by Govorov based on the density-matrix formalism, where a chiral molecule is treated as a two-level system with nonorthogonal magnetic and electric dipole moments and subsequently the CD spectrum of the hybrid molecule-NC complex can be rigorously calculated as the total contribution from the molecule and the NC. [44,45] In the second approach, Zhang and co-workers simply considered the plasmonic absorption as the dominant contribution to the overall CD of the hybrid system, where the chiral molecule is regarded as an electric dipole with different effective polarizabilities for LCP and RCP excitation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…[44,45] In the second approach, Zhang and co-workers simply considered the plasmonic absorption as the dominant contribution to the overall CD of the hybrid system, where the chiral molecule is regarded as an electric dipole with different effective polarizabilities for LCP and RCP excitation. [46,47] As discussed below, this method represents a classical point of view of isotropic chiral medium, and can be derived from Govorov's quantum treatment by considering Fedorov [61] and Rosenfeld's equations. [62]…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently,c hiral assemblies,p articularly chiroplasmonic assemblies,h ave been shown to display the unique activity of strong polarization rotation, which makes them ar emarkable new class of chiroptical materials. [20][21][22][23] Circular dichroism (CD) peaks in the visible/near-infrared window were found to change from negative to positive in the process of uptake due to as pontaneous twisting motion around the bridged DNAwhen the nanoparticle dimers move from the interstitial fluid to the cytosol. [24,25] This interesting property could enable chiroplasmonic assemblies to be used as intra/ extracellular biosensors for the detection of multiple metal ions using handedness-dependent CPL.…”
mentioning
confidence: 99%